O Marco Referencial da rede municipal de ensino de Sorocaba: análise do escrito e de sua influência no trabalho docente, à luz de Paulo Freire - Bravo, Daniela Gaete Sewaybricker (2017)
This study aims to study the Referential Framework of the Sorocaba municipal school network and aims to verify the extent to which the presence of Paulo Freire's Liberating Education, present in the Referential Framework of the Municipal Education Network of Sorocaba, is aligned with the teaching work of school units. It presents a qualitative approach and made use of some instruments of data collection and analysis. We used bibliographical research, documentary analysis structured in a Discursive Textual Analysis (DTA) approach and questionnaires with open and closed questions, which were applied to educators of the Sorocaba-SP municipal school system. Thus, we used the bibliographical research to present the Sorocaba Referential Framework and the process of its elaboration, as well as to highlight and characterize Paulo Freire's Liberating Education assumptions related to the fundamentals of the Frankfurt School and Critical Theory. Later, the conception of Education of Freire, the Liberating Education, was made explicit. The analysis of the Referential Framework was carried out through the discursive textual analysis, which culminated in the systematization of metatexts organized into two broad emerging categories: Extracts that refer to Freire and Extracts that do not refer to Freire. Beyond these broad categories, some subcategories emerged: dialogicity, awareness, education, problematization and emancipation. We also conducted a field survey through the application of questionnaires (with open and closed questions) to the teachers, in order to relate the analysis of the document to the interpretations of the reality experienced in the municipal schools of Sorocaba.